Application of chemotactic behavior for life detection - Riekeles, Max; Bruder, Vincent; Adams, Nicholas; Santos, Berke; Schulze-Makuch, Dirk (Frontiers in Astronomy and Space Sciences, 2025)
One excellent biosignature for the present detection of microbial life on Earth is motility, leading to its growing interest within the astrobiological community as an observable attribute that, if detected during future in situ space missions, could point towards the existence of life on Mars or other celestial bodies. Microbial motility can be induced by various stimulants, including certain chemicals called chemoeffectors, leading to subsequent chemotaxis. Following this concept, this work examines the chemotactic affinities of the bacteria Bacillus subtilis and Pseudoalteromonas haloplanktis as well as the archaeon Haloferax volcanii for L-serine, which has been previously demonstrated to have a high chemoeffective potency across a wide range of species from all domains of life on Earth. Methodologically, we introduce here a novel approach for utilizing µ-slides that diverges from the more traditional long-term chemotactic assay in favor of a shorter time frame assay that only requires a simple blob detection algorithm for microbial detection. Given the technical, computational, and time constraints necessary for an in-situ life detection mission, this simplified approach could be a cost and resource-effective way to probe for potential chemotactic-responsive life. Overall, the results indicated that each of the three organisms showed chemotactic behavior toward L-serine, which, to our knowledge, is the first time that an L-serine-induced chemotactic response has been detected for H. volcanii.